First records of Henricia obesa (Sladen, 1889) (Asteroidea: Echinasteridae) in the Peruvian sea - Paredes, Carlos (2006)
The star sea Henricia obesa (Sladen, 1889) (Asteroidea: Echinasteridae) is reported for the first time from Peruvian sea.